Addressing police discrimination regarding mental distress using a service user-led and interpersonal contact/education based 'e-Learning'. (15th January 2021) - Davey, Steven; Gordon, Sarah; Tester, Rachel
ABSTRACT: In recent years, the New Zealand Police have seen a significant increase in mental health related calls. In accord with best practice anti-discrimination interventions, three service user-led and interpersonal contact/education-based e-Learning modules were developed and delivered to police staff to counter discrimination and effect behaviour change. A formative evaluation of the e-Learning was undertaken using semi-structured interviews with 24 police staff who had completed the e-Learning modules within the previous 6–12 months. A number of themes emerged from the data that suggest the e-Learning could be used to develop enhanced intrapersonal attitudes and behaviours in relation to people experiencing mental distress, and to encourage increases in the well-being of police themselves. However, the data also suggested a number of barriers to implementing the e-Learning in order to effect changes in facilitating a police response. These barriers include widespread issues of limited resourcing and difficulties with inter-agency working.